Bimetallic CoCu catalyst derived from in-situ grown Cu-ZIF-67 encapsulated inside KIT-6 for higher alcohol synthesis from syngas. (15th October 2020) - Li, Zhuoshi; Luo, Guangyuan; Chen, Tao; Zeng, Zhuang; Guo, Shaoxia; Lv, Jing; Huang, Shouying; Wang, Yue; Ma, Xinbin
Graphical abstract: Highlights: A CoCu catalyst derived from KIT-6-encapsulated ordered MOF precursor was prepared. The as-prepared catalyst showed superior performance and excellent stability in HAS. The ordered MOF benefits high dispersion and uniform distribution of Co and Cu sites. Both CO dissociation and synergy between CO dissociation and insertion were enhanced. Abstract: Higher alcohol synthesis (HAS) from syngas is a promising route for converting fossil energy resources into useful fuels or chemicals. Design and fabrication of efficient CoCu catalysts for HAS is mainly focused on promoting the close cooperation and high dispersion of Co and Cu species. Here, a highly dispersed CoCu bimetallic catalyst encapsulated in mesopores derived from in-situ grown ordered Zeolitic Imidazolate Frameworks (ZIFs) inside KIT-6 was proposed, and applied in HAS. With optimized Co/Cu ratio, the as-prepared Co4 Cu1 -Z@KIT-6 catalyst obtained a CO conversion of 39.7% and a space time yield (STY) towards C2+ alcohols of 11.1 mmol‧gcat −1 ‧h −1, which can be 2 and 3 times as high as those of the Co4 Cu1 -G@KIT-6 catalyst derived from amorphous CoCu glyoxylate complex precursor, respectively. And no visible deactivation was detected over 160 h reaction. Benefiting from inheriting the periodically and orderly arranged bimetallic sites of Cu modified ZIF precursors, it was demonstrated that the high dispersion, uniform distribution and close interaction of Co and Cu species can be achieved in Co4 Cu1 -Z@KIT-6. Moreover, it was further proved that the order degree of catalyst precursor has great influence on CO adsorption. Not only the CO bridge-type adsorption sites with high CO dissociation capabilities were favored in Co4 Cu1 -Z@KIT-6, but also promoted synergistic catalysis between the CO dissociation and CO insertion sites can be achieved, which contribute to the enhanced performance in HAS. This work may provide new insights for further design and synthesis of high-performance CoCu catalysts for HAS.